Effects of botulinum toxin type A facial injection on monoamines and their metabolites in sensory, limbic and motor brain regions in rats. (23rd March 2016) - Ibragić, S.; Matak, I.; Dračić, A.; Smajlović, A.; Muminović, M.; Proft, F.; Sofić, E.; Lacković, Z.; Riederer, P.
Highlights: Effects of Botulinum toxin A (BTX-A) on central monoamines and their metabolites were analyzed. Antinociceptive effects of BTX-A are most probably not related to central monoamine concentrations. Monoamine hypothesis: low levels of serotonin (5-HT), noradrenaline (NA) and/or dopamine (DA) linked to depression. Observed increased NA and 5-HT concentrations might play a role in BTX-A efficacy for treatment of depression. Changes in neurotransmission by BTX may be able to influence depression, sleep and pain. Abstract: Despite its toxicity, botulinum neurotoxin type A (BTX-A) is a valuable therapeutic agent for several motor, autonomic and pain disorders. Numerous studies have described its peripheral as well as central effects. Using reversed-phase High Performance Liquid Chromatography with Electrochemical Detection (HPLC-ED) and gradient elution, we quantified the concentrations of dopamine (DA), noradrenaline (NA), serotonin (5-HT) and their metabolites in 10 brain regions, ipsilateral and contralateral from the site of unilateral BTX-A administration (5 U/kg) into the rat whisker pad. In regions associated with nociception and pain processing we also examined possible BTX-A effects in combination with formalin-induced inflammatory orofacial pain. The dominant BTX-A effects on the monoamines and their metabolites were insignificant. The only significant increase caused by BTX-A alone was that of NA in striatum and serotonin in hypothalamus. While antinociceptive effects of BTX-A are most probably not related to central monoamine concentrations, the localized increased NA and 5-HT concentrations might play a role in reported BTX-A efficacy for the treatment of depression.